Factors affecting the Entrepreneurial Intention of Universities’ Students: Case study with Students at Can Tho University of Technology, Vietnam. - Nguyen, Phuong; Pham , Nam; Huynh, Binh (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2025)
This study examines the factors that affect the entrepreneurial intention of universities’ students in Vietnam. We do a case study with the students at Can Tho university of Technology (CTUT). We do a survey with 925 students at CTUT (with 60% of the sample being from non-economic students) and treat the data with SPSS version 27. We use SEM for testing the Linear structural model. The results show that factors that positively influence students' intention to start a business include: (1) Social Norms; (2) Knowledge and Experience; (3) Social Norms; (4) Personal Attitude; and (5) Personal Traits. Interestingly, (6) Educational Support negatively affects the students' intention to start a business. This may be explained by the large difference in applying educational knowledge into entrepreneurial activity between economic students and non-economic ones. The results may provide the orientations so that managers and the government correctly motivate start-up activities in university students.